2011
DOI: 10.1371/journal.pone.0018344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Audiovisual Training on Monaural Spatial Hearing in Horizontal Plane

Abstract: The article aims to test the hypothesis that audiovisual integration can improve spatial hearing in monaural conditions when interaural difference cues are not available. We trained one group of subjects with an audiovisual task, where a flash was presented in parallel with the sound and another group in an auditory task, where only sound from different spatial locations was presented. To check whether the observed audiovisual effect was similar to feedback, the third group was trained using the visual feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 86 publications
(107 reference statements)
2
85
1
Order By: Relevance
“…Thus, synchronous audiovisual training enhances the recovery of accurate sound localization by human subjects wearing a unilateral earplug [85], and improves the perception of spectrally degraded speech by listeners with normal hearing [86]. These findings suggest that it might be beneficial to combine visual and auditory cues in the rehabilitation of the hearing impaired.…”
Section: Visual Influences On Auditory Spatial Plasticitymentioning
confidence: 78%
“…Thus, synchronous audiovisual training enhances the recovery of accurate sound localization by human subjects wearing a unilateral earplug [85], and improves the perception of spectrally degraded speech by listeners with normal hearing [86]. These findings suggest that it might be beneficial to combine visual and auditory cues in the rehabilitation of the hearing impaired.…”
Section: Visual Influences On Auditory Spatial Plasticitymentioning
confidence: 78%
“…It is of importance that a visuo‐auditory synergy can lead to the improvement in unimodal speech processing, either auditory or visual. Indeed, audio‐visual practice allows a significant increase in perceptual performance in a single modality alone (Frassinetti et al ., ; Seitz et al ., ; Strelnikov et al ., ). Our recent study demonstrated an increase in speech‐reading skills in CI patients during the first months of experience of the implant (Strelnikov et al ., ), suggesting that a strong positive feedback consolidates the decoding of visual cues with auditory information resulting in an increase in speech‐reading performance.…”
Section: Discussionmentioning
confidence: 99%
“…Strelnikov et al reported the effect of previous localization training on monaural hearing [5], and Slattery and Middlebrooks reported that a few congenitally monaural deaf people are able to localize sound generally over 360…”
Section: Discussionmentioning
confidence: 99%